ANALISIS KETEPATWAKTUAN PENYAMPAIAN LAPORAN KEUANGAN ORGANISASI PERANGKAT DAERAH (STUDI KASUS PADA BEBERAPA ORGANISASI PERANGKAT DAERAH PEMERINTAH KABUPATEN HALMAHERA BARAT) - Sipolo, Gerall Henry; Gamaliel, Hendrik; Korompis, Claudia W. M. (Universitas Sam Ratulangi, 2024)
This research aims to determine and analyze the timeliness of submission of financial reports of regional apparatus organizations and also the factors that influence the inaccuracy of submission of financial reports of Regional Apparatus Organizations. Research was conducted at several West Halmahera Regency Regional Apparatus Organizations, namely at the Education and Culture Service, the Public Works and Spatial Planning Service, and the Health Service. The type of data used in this research is primary data and secondary data. This research uses qualitative descriptive analysis techniques. The results of the analysis from this research are that the submission of financial reports to several regional organizations in West Halmahera Regency is still not on time in accordance with Government Regulation number 12 of 2019 and Minister of Home Affairs Regulation Number 77 of 2020. This is influenced by several factors, namely resource competency humans who are inadequate in technology-based financial management as well as educational backgrounds that are not appropriate to their field, the use of software that does not have complete features nor is it integrated between software, and in the implementation of organizations that have not implemented procedures related to submitting accountability reports from the field -fields in the agency, and the use of information technology that does not yet have complete features.